Тенденции в трансформации российских элит: новые подходы и интерпретации - Андрей Швая (ЖУРНАЛ СОЦИОЛОГИИ И СОЦИАЛЬНОЙ АНТРОПОЛОГИИ, 2020)
The Eighteenth All-Russian Seminar "Sociological Problems of Power Institutions in the Conditions of Russian Transformation", organized by the Sociological Institute of the Russian Academy of Sciences with the participation of the Russian Association of Political Science, was held in St. Petersburg on October 24-26, 2019. The presented reports were addressed both to general topics in the study of elites (recruiting issues, relations between federal and regional power groups, power dispositions of local elites, etc.), and to more specific problems that are poorly embedded in the established range of issues of modern Russian elite studies.